Characteristics and outcome of long-stay patients in a paediatric intensive care unit in Cape Town, South Africa - Nupen, Tracey Lee (Department of Paediatrics and Child Health, 2016)
Objectives: To describe a rational basis for the definition of a long-stay patient (LSP) in a South African paediatric intensive care unit (PICU); to review the characteristics and outcomes of the patients who comply with the LSP definition; to assess the proportion of resources allocated to the LSP cohort; and to determine if the results of this study could be used as a predictive tool for future admissions. Methods: A retrospective descriptive study of routine data collected over one calendar year (2009) from a 20-bedded multidisciplinary PICU was conducted. The definition of a LSP in this setting was established using various models. The characteristics and outcomes of the long- and short- stay groups were compared using nonparametric Mann-Whitney U and Chi2 tests, with significant results entered into a stepwise multiple regression model. The proportion of ICU days consumed by LSP was calculated. Human Research Ethics Committee approval was obtained (Ref/Rec 105/2011).